IMPLEMENTASI JARINGAN FIBER TO THE HOME DENGAN TEKNOLOGI GIGABIT PASSIVE OPTICAL NETWORK DI PT ENVISION - Alpo Gianta; Imam Farisi (PT. Hasba Edukasi Mandiri, 2025)
The rapid development of telecommunications technology drives the need for faster and more stable internet networks. One solution that is widely implemented is the Fiber to the Home (FTTH) network with Gigabit Passive Optical Network (GPON) technology. This study discusses the implementation of a GPON-based FTTH network in PT Envision, which aims to improve the quality of internet services for tenants and visitors. The methods used in this implementation include designing network topology, selecting Optical Line Terminal (OLT) and Optical Network Terminal (ONT) devices, as well as the network installation and configuration process. The implementation results show that GPON technology is able to provide high-speed internet connections, low latency, and efficiency in bandwidth distribution. By using passive architecture, this network is also more energy efficient and operational cost efficient compared to conventional copper cable technology. The successful implementation of the FTTH network with GPON in PT Envision Bekasi is expected to be a reference for shopping centers or other commercial areas in improving their telecommunications infrastructure.